Characteristics extraction and numerical analysis of the rough surface macro-morphology. Issue 3 (8th April 2019) - Sun, Qingchao; Mu, Xiaokai; Yuan, Bo; Xu, Jiawen; Sun, Wei
Abstract : Purpose: This paper aims to distinguish the relationship between the morphology characteristics of different scales and the contact performance of the mating surfaces. Also, an integrated method of the spectrum analysis and the wavelet transform is used to separate the morphology characteristics of the actual machined parts. Design/methodology/approach: First, a three-dimensional (3D) surface profilometer is used to obtain the surface morphology data of the actual machined parts. Second, the morphology characteristics of different scales are realized by the wavelet analysis and the power spectral density. Third, the reverse modeling engineering is used to construct the 3D contact models for the macroscopic characteristics. Finally, the finite element method is used to analyze the contact stiffness and the contact area of the 3D contact model. Findings: The contact area and the nominal contact pressure Pn have a nonlinear relationship in the whole compression process for the 3D contact model. The percentage of the total contact area of the macro-scale mating surface is about 70 per cent when the contact pressure Pn is in the range of 0-100 MPa, and the elastic contact area accounts for the vast majority. Meanwhile, when the contact pressure Pn is less than 10MPa, the influence factor (the relative error of contact stiffness) is larger than 50 per cent, so the surface macro-scale morphology has a weakening effect on the normal contact stiffness of the mating surfaces. Originality/value: This paper provides an effective method for the multi-scale separation of the surface morphology and then lays a certain theoretical foundation for improving the surface quality of parts and the morphology design.